Outside - Holm, Jennifer L. (Scholastic Press, 2025)
From three-time Newbery Honor winner Jennifer L. Holm, a chilling but heartfelt story set in the near future somewhere in North America. Razzi is being raised in a compound who doesn't understand how isolated and unusual her life is... until she must encounter the outside world. Whatever you do, don't leave home. Razzi has always been told: Don't go Outside. It isn't safe. There are people and creatures out there that will harm you. The walls of the Refuge will protect you from them. Razzi's friend Ollie was curious about Outside... and it led to his death. So Razzi is trying to be on her best behavior. She is the oldest kid left, the one the younger kids look up to. She has to follow the rules. But Outside has a way of getting in, and Razzi, guided by a dog she has a strangely close connection with, wonders what it's like to run free beyond the walls. If she steps away from everything she's ever known... what will she find?